2014
DOI: 10.1371/journal.pone.0106224
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Inhibitor, Vorinostat, Represses Hypoxia Inducible Factor 1 Alpha Expression through Translational Inhibition

Abstract: Hypoxia inducible factor 1α (HIF-1α) is a master regulator of tumor angiogenesis being one of the major targets for cancer therapy. Previous studies have shown that Histone Deacetylase Inhibitors (HDACi) block tumor angiogenesis through the inhibition of HIF-1α expression. As such, Vorinostat (Suberoylanilide Hydroxamic Acid/SAHA) and Romidepsin, two HDACis, were recently approved by the Food and Drug Administration (FDA) for the treatment of cutaneous T cell lymphoma. Although HDACis have been shown to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 63 publications
3
63
2
2
Order By: Relevance
“…Thus, our results demonstrate that HDAC6 depletion acetylates HIF-1α and promotes HIF-1α degradation under hypoxia. In agreement with this finding, the HDAC6-selective inhibitor Tubastatin A (Schoepflin et al 2016) and pan-HDACi SAHA (Hutt et al 2014) blocked HIF-1α activity via a direct effect on HIF-1α stability via its acetylation and degradation. These data suggest that HDAC6 directly binds to and deacetylates HIF-1α.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, our results demonstrate that HDAC6 depletion acetylates HIF-1α and promotes HIF-1α degradation under hypoxia. In agreement with this finding, the HDAC6-selective inhibitor Tubastatin A (Schoepflin et al 2016) and pan-HDACi SAHA (Hutt et al 2014) blocked HIF-1α activity via a direct effect on HIF-1α stability via its acetylation and degradation. These data suggest that HDAC6 directly binds to and deacetylates HIF-1α.…”
Section: Discussionsupporting
confidence: 75%
“…Stable HIF-1α translocates to the nucleus, dimerizes with HIF-1β, and activates the transcription of target genes that contain a hypoxia response element (HRE). Several studies using cancer cell lines have described a role for HDACs in regulating the stability and activity of HIF-1α Geng et al 2011;Hutt et al 2014;Kong et al 2006;Qian et al 2006), although the mechanisms of action vary widely according to cell type. For example, class II HDAC6 and HDAC4 are associated with HIF-1α, and inhibition of both HDACs reduces HIF-1α protein levels (Geng et al 2011;Kong et al 2006;Qian et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Promotion of the glycolytic pathway is known as the Warburg effect, providing efficient cellular energy production in cancers including HCC35. Therefore, this phenomenon of glycolysis reduction was presumably associated with the induction of the expression of tumor suppressor genes that reduce glycolysis (Supplementary Figure S5A), and inhibition of metabolic oncogenes, as exemplified by hypoxia inducible factor1α in Huh7 cells36. Moreover, the glycolysis was possibly halted at late stages, as deduced from the accumulated Ala and lactic acid from pyruvic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Its downstream target genes, pathways and proteins can regulate the cell response due to a hypoxia-like stimulation [20]. HIF-1 is composed of the HIF-1α and HIF-1 β subunits; the latter is constitutively expressed in the nucleus, whereas HIF-1α is regulated by the environment [2123]. Besides hypoxia, HIF-1α can be activated by environmental stimuli under normoxic conditions [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1 is composed of the HIF-1α and HIF-1 β subunits; the latter is constitutively expressed in the nucleus, whereas HIF-1α is regulated by the environment [2123]. Besides hypoxia, HIF-1α can be activated by environmental stimuli under normoxic conditions [23,24]. Previous studies have found that the stability and function of HIF-1 is primarily regulated by posttranslational modifications [24].…”
Section: Introductionmentioning
confidence: 99%